Study of red cell indices and reticulocyte count in person with anemia at a tertiary care hospital of Kathmandu - Pudasaini, Sujata; Pant, PP; Kafle, N; Maharjan, S; KC, A; Shrestha, S (Nepal Medical College Journal, 2019)
Anemia is not a disease but a clinical feature of some other underlying problems. It is one of the most common public health problems in developing countries. The prevalence of anemia differs according to the age group. A cross sectional observational study was conducted in a tertiary hospital, over a period of six months (January 2018 to June 2018). All the cases of anemia in different age group with hematological investigations (hemoglobin and red blood cell indices) including reticulocyte count during the study period were included. A total of 274 blood samples of persons with anemia were evaluated. The mean age of the patients was 41.4 ± 25.37 years. Anemia was more commonly seen in females (68.2%) than males (31.8%) in our study. The most affected age group for anemia was person ≥ 15 years followed by children < 5 years. The least affected group was children of 12- 14 years. Microcytic anemia (decreased MCV and decreased MCHC) was observed in children of 12- 14 years and macrocytic anemia (increased MCV) was seen in group ≥ 15 years. Red cell distribution width (RDW) was more elevated in children of 12 -14 years and showed that there was significant variation of size of RBC in this group. Reticulocyte count was higher in children < 5 years and lower in children of 12- 14 years. Significant correlation was noted for hematocrit and reticulocyte count. This study revealed that the prevalence of anemia increases with age and was more common in females. Baseline study of red blood cell indices and reticulocyte count will help us in diagnosing the type of anemia and in further management.